2006
DOI: 10.1021/es0603406
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Organic Wastewater Contaminants in Biosolids Destined for Land Application

Abstract: In this study, the presence, composition, and concentrations of organic wastewater contaminants (OWCs) were determined in solid materials produced during wastewater treatment. This study was undertaken to evaluate the potential of these solids, collectively referred to as biosolids, as a source of OWCs to soil and water in contact with soil. Nine different biosolid products, produced by municipal wastewater treatment plants in seven different states, were analyzed for 87 different OWCs. Fifty-five of the OWCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
229
2
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(244 citation statements)
references
References 64 publications
8
229
2
3
Order By: Relevance
“…The concentrations of macrolides detected in the sludge in this study were lower than those previously reported in Hong Kong (ERY: 63 μg/kg) (Xu et al, 2007), USA (ERY: 41 μg/kg) (Kinney et al, 2006) and Spain (ERY: 62.5 μg/kg; TYL: 1074 μg/kg) (Radjenović et al, 2009), indicating that the levels of macrolides pollution in this study were relatively low.…”
Section: Macrolidescontrasting
confidence: 85%
See 1 more Smart Citation
“…The concentrations of macrolides detected in the sludge in this study were lower than those previously reported in Hong Kong (ERY: 63 μg/kg) (Xu et al, 2007), USA (ERY: 41 μg/kg) (Kinney et al, 2006) and Spain (ERY: 62.5 μg/kg; TYL: 1074 μg/kg) (Radjenović et al, 2009), indicating that the levels of macrolides pollution in this study were relatively low.…”
Section: Macrolidescontrasting
confidence: 85%
“…It was reported that the concentrations of antibiotics ranged from μg/kg to a few mg/kg in sewage sludge from different countries, such as Estonian (Lillenberg et al, 2009), Italy (Zuccato et al, 2010), Spain (Nieto et al, 2010;Radjenović et al, 2009), Switzerland (Göbel et al, 2005), USA (Kinney et al, 2006), Japan (Okuda et al, 2009) and China (Xu et al, 2007). In China, there are over 30 million tons of sewage sludge (moisture content: 80%) generated in 2011, and 75-85% of them cannot be safely disposed (Zou and Wang, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…PPs have been massively used and are considered emergent contaminants because they have been introduced in soils and waters through (i) human excretions in sewage collectors (especially from hospital effluents (Heberer, 2002)), (ii) disposal of unwanted, unused or expired products in the toilet or sink, and (iii) land application of animal manure (O'Connor and Aga, 2007) and treated sewage sludge (Kinney et al, 2006). PPs have been detected (at ng L − 1 and μg L − 1 levels) in a wide variety of water samples, such as effluents (from medical care units, landfills, and municipal sewage), seawater, drinking water, and surface-and groundwater, (Benotti et al, 2009;Fatta-Kassinos et al, 2011); but also in soils and sediments in concentrations ranging from μg kg − 1 to mg kg − 1 (Braganca et al, 2012;Li et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…15 Sewage sludge used as fertilizers might contaminate crops, soils, superficial and underground waters with nitrates, heavy metals, pathogens, various classes of organic compounds and persistent organic compounds. 14,16,17 In Brazil, the use of SS in agriculture is regulated through the directive CONAMA357/2005. 18 There is little information in the literature about PAH uptake by plants from SS-treated soils.…”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic organic contaminants, including several PAHs, have been found in soils amended with sewage sludges. 17 Experimentally validated mathematical models can demonstrate or predict the soil contamination with persistent organic pollutants from SS continuously used as agricultural fertilizer. Physicochemical characteristics such as water solubility, lipid affinity, vapor pressure, soil organic carbon sorption and half-life of organic compounds allow developing mathematical models that can predict risks of soil contamination by continuous SS applications.…”
mentioning
confidence: 99%